Educational Theory Review: Contemporary Perspectives - Firman Firman; Ainun Latifah S; Sri Julianti; Haerul Anugerah; Julkarnain Julkarnain; Muh. Natsir; Faisal Faisal (Journal of Indonesian Progressive Education, 2026)
The examination of the review of educational theory is covered in this article. Education is a crucial procedure in determining the caliber of human resources and maximizing each person's potential. The dynamics of learning, scientific advancements, and shifting cultural demands gave rise to a variety of educational philosophies. Thus, it is crucial to analyze different educational theories in order to comprehend the pedagogical, psychological, and philosophical underpinnings of education. The purpose of this study is to evaluate the many educational ideas that have evolved over time, pinpoint the traits, benefits, and drawbacks of each theory, and assess its applicability to modern teaching methods.  Through the examination of several books, scientific publications, and pertinent scholarly sources, the study employs a qualitative approach with the library research method. The analysis's findings demonstrate how several educational theories, including constructivism, behaviorism, cognitivism, and humanism, contribute differently to the explanation of the teaching and learning process. Every theory has a unique viewpoint on the roles of teachers, students, learning methods, and educational objectives. An integrative approach is required based on the characteristics of students and the learning setting because no single theory can adequately address all educational difficulties.